Complement-Inhibiting Therapy of Atypical Haemolytic Uremic Syndrome in a Patient With Factor H Mutation - Irina N. Lupan; Alexander Yu. Pischalnikov; Hadizha M. Emirova; Ekaterina S. Stolyarevich; Alexander M. Volyansky; Larisa V. Glukhova (Union of pediatricians of Russia, 2019)
Atypical haemolytic uremic syndrome (aHUS) is an extremely rare pathology with the development of complement-mediated thrombotic microangiopathy (TMA). Before eculizumab, a humanized IgG monoclonal antibody to the complement component C5, the prognosis of total and renal survival with aHUS was unfavourable due to the high probability of death and the development of end-stage chronic renal failure in surviving patients. This article presents a clinical observation of a patient with aHUS who had an identified heterozygous factor H (CFH) mutation - c.3653G>A(p.Cys1218Tyr), and two heterozygous variants of polymorphism in the same gene - c.2016A>G; c.2808G>T. Despite the achievement of haematological remission of TMA against the background of plasma therapy, the child developed dialysis-dependent renal failure. Treatment with eculizumab in a patient with chronic kidney damage provided a significant improvement in their function, maintaining a stable remission and improving the quality of life of the patient with aHUS.Kh. М. Emirova, Е. S. Stolyarevich take part in educational events for doctors as lecturers with the support of Alexion Pharma. The other contributors confirmed the absence of a reportable conflict of interest.